Hypermyelination of the left auditory cortex in developmental dyslexia. (6th February 2018) - Skeide, Michael A.; Bazin, Pierre-Louis; Trampel, Robert; Schäfer, Andreas; Männel, Claudia; von Kriegstein, Katharina; Friederici, Angela D.
Abstract : Objective: Cortical malformations are documented postmortem in speech processing areas of the dyslexic human brain. The goal of this pilot study was to find out if such anatomic anomalies can be detected noninvasively and in vivo. Methods: We developed a reconstruction of left perisylvian cortex profiles at a resolution of 400 μm using T1 data acquired with ultra-high-field MRI at 7T. Cortical thickness, myelinated cortical thickness, and layer-wise myelination were then compared in 6 men with developmental dyslexia and 6 healthy controls matched for age, sex, handedness, education level, and nonverbal IQ. Results: Compared to healthy controls, dyslexic individuals showed comparable cortical thickness ( t [1, 10] = 1.98, p = 0.311) but significantly increased myelinated cortical thickness ratio ( t [1, 10] = 3.85, p = 0.013, familywise error–corrected, Cohen d = 2.03), resulting in an area under the receiver operator characteristic curve of 0.944 ( p = 0.010, standard error 0.067, 95% confidence interval 0.814–1). Moreover, T1 relaxation, especially in layer IV of the left auditory cortex, was also significantly increased ( t [1, 10] = 3.32, p = 0.043, familywise–error corrected, Cohen d = 1.67). Conclusions: Our findings provide critical insights into the neurobiological manifestation of the most common learning disorder and suggest that our approach might also shed new light on other neurodevelopmental disorders associated with cortical abnormalities.